Aportaciones a la flora de la provincia de Segovia (España) III - Sobrino, Eduardo; Dana, Elías D.; Sanz-elorza, Mario (Botanica Complutensis, 2006)
In this paper, floristic and chorological data about eleven vascular plants species in the Community of Castilla-León are presented. Most of these species are aliens. Urtica pilulifera L., Lepidium perfoliatum L., Duchesnea indica (Jacks.) Focke, Chaenomeles speciosa (Sweet) Nakai, Laburnum anagyroides Medik. subsp. anagyroides, Abutilon theophrasti Medik., Epilobium brachycarpum C. Presl and Lycium barbarum L. are first records for Segovia province. Datura innoxia Miller has been recorded for the first time in the province of Valladolid. Lathyrus sativus L. has been recorded for the first time in the province of Ávila. Hemerocallis fulva (L.) L. has been recorded for the second time in the province of Segovia. Also, the distribution maps (10 x 10 km UTM cells) of all species are provided .